If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -3 = 2(-1 + 1) Reorder the terms: -3 + y = 2(-1 + 1) Combine like terms: -1 + 1 = 0 -3 + y = 2(0) Multiply 2 * 0 -3 + y = 0 Anything times zero is zero. -3 + y = 0 Solving -3 + y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + y = 0 + 3 Combine like terms: -3 + 3 = 0 0 + y = 0 + 3 y = 0 + 3 Combine like terms: 0 + 3 = 3 y = 3 Simplifying y = 3
| 7(10)+7(10)+12(10)=360 | | 3+x+5-2x=78 | | 4x(2x-7)=112 | | 3x+5[2-4(x-2)]=x-4 | | 24v^4+78v^3b-21v^2b^2=0 | | Y=2ax-9x-9b | | 3+x-5+2x=78 | | -3[x+(-8)]=56 | | 4x+17=2x | | 126=10+4p | | 7x+42=-18-3x | | F(x)=11x-1 | | [x-2]=-2 | | 195=12+x | | 2y=103-x | | 5(x+5)+8(-x+8)=77 | | 3x-15+6x+1=45 | | -4(x-1)=9x+9 | | .5(10+12n)=.3333(15n+15) | | -4(x+6)=-4(x+2)-x | | 8(5c-1)-18=38c+8 | | -1=t+(-18) | | 8c^2-20c-12=0 | | 3.5(9)+3.5(9)+12(9)=180 | | 9x-6x-2=1 | | y=x^3-13x | | 7x+1=-2x+37 | | 6t+3(5t-4)=12(2t-2w) | | -16x-3=x-67 | | n^2+7.58333333333n=0 | | 6+3(5t-4)=12(2t-2w) | | 10x+-8=22 |